THE INFLUENCE OF SERVICE QUALITY AND PRICE ON CONSUMER INTEREST IN USING TRANSPORTATION SERVICES LRT IN PALEMBANG CITY - Cindi Pramita; Sella Herlinia; Maya Panorama (Jurnal Ekonomi, 2023)
Transportation is considered a driver of the life of an area because itprovides a crucial link of the population that continues to move in the areaand then encourages regional formation and growth. not all peoplecontribute to the utilization of lrt transportation services, especially inPalembang City, because there is still a lack of travel routes that makeconsumers reluctant to transit to their destination and prefer other landtransportation services. But there is also a positive thing that there aresome people who contribute to utilizing lrt services, especially those on oneroute and curiosity.This research was conducted on 97 respondents.Themethod used in this study uses quantitative methods using correlationalstudies, survey research, data quality tests, validity tests, multiple linearregression and hypothesis testing. The results of this study indicate that thevariables of service quality and price have a positive effect on the variable ofinterest in the use of transportation services at Palembang City.